Impact of Clean Delivery-kit use on Newborn Umbilical Cord and Maternal Puerperal Infections in Egypt (Journal of Health, Population and Nutrition, 2010)
This cross-sectional cohort study explored the impact of the use of clean delivery-kit (CDK) on morbidity due to newborn umbilical cord and maternal puerperal infections. Kits were distributed from primary-care facilities, and birth attendants received training on kit-use. A nurse visited 334 women during the first week postpartum to administer a structured questionnaire and conduct a physical examination of the neonate and the mother. Results of bivariate analysis showed that neonates of mothers who used a CDK were less likely to develop cord infection (p=0.025), and mothers who used a CDK were less likely to develop puerperal sepsis (p=0.024). Results of multiple logistic regression analysis showed an independent association between decreased cord infection and kit-use [odds ratio (OR)=0.42, 95% confidence interval (CI) 0.18-0.97, p=0.041)]. Mothers who used a CDK also had considerably lower rates of puerperal infection (OR=0.11, 95% CI 0.01-1.06), although the statistical strength of the association was of borderline significance (p=0.057). The use of CDK was associated with reductions in umbilical cord and puerperal infections. Key words: Cohort studies; Cross-sectional studies; Delivery-kit; Evaluation studies; Impact studies; Morbidity; Sepsis; Umbilical cord infections; Egypt DOI: 10.3329/jhpn.v27i6.4326 J Health Popul Nutr 2009 Dec; 27(6): 746-754